Engineering an anaerobic metabolic regime in Pseudomonas putida KT2440 for the anoxic biodegradation of 1,3-dichloroprop-1-ene - Nikel, Pablo Ivan (2013)
Pseudomonas putida KT2440, a microbial cell factory of reference for industrial whole-cell biocatalysis, is unable to support biochemical reactions that occur under anoxic conditions, limiting its utility for a large number of relevant biotransformations. Unlike (facultative) anaerobes, P. putida resorts to NADH oxidation via an oxic respiratory chain and completely lacks a true fermentation metabolism. Therefore, it cannot achieve the correct balances of energy and redox couples (i.e., ATP/ADP and NADH/NAD+) that are required to sustain an O2-free lifestyle. To overcome this state of affairs, the acetate kinase (ackA) gene of the facultative anaerobe Escherichia coli and the pyruvate decarboxylase (pdc) and alcohol dehydrogenase II (adhB) genes of the aerotolerant Zymomonas mobilis were knocked-in to a wild-type P. putida strain. Biochemical and genetic assays showed that conditional expression of the entire enzyme set allowed the engineered bacteria to adopt an anoxic regime that maintained considerable metabolic activity. The resulting strain was exploited as a host for the heterologous expression of a 1,3-dichloroprop-1-ene degradation pathway recruited from Pseudomonas pavonaceae 170, enabling the recombinants to degrade this recalcitrant chlorinated compound anoxically. These results underscore the value of P. putida as a versatile agent for biotransformations able to function at progressively lower redox statuses.